Faculty Senate, Minutes, November 20, 2003 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2003)
Valdosta State University. Faculty Senate, Minutes, November 20, 2003. Chairman, Ron Zaccari Ron Zaccari; Vice Chairman, Louis Levy; Executive Secretary, David Boyd; Parliamentarian, Mike Meacham;
1 electronic document. Valdosta State University. Faculty Senate, Minutes, November 20, 2003. 9 pages. 186,448 bytes.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records